2014
DOI: 10.1089/acm.2014.0080
|View full text |Cite
|
Sign up to set email alerts
|

Hair Cortisol as a Biomarker of Stress in Mindfulness Training for Smokers

Abstract: These preliminary findings suggest that smoking cessation intervention is associated with decreased hair cortisol levels and that reduced hair cortisol may be specifically associated with mindfulness training and smoking abstinence. RESULTS support the use of hair cortisol as a novel objective biomarker in future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 36 publications
1
31
0
2
Order By: Relevance
“…Dual diagnosis with concurrent treatment of PTSD and substance use disorder has demonstrated overall improvement in outcomes (Back, Waldrop, Brady, & Hien, 2006; Mills et al, 2012; Najavits, Weiss, Shaw, & Muenz, 1998), but broader application of stress amelioration techniques may be advantageous in this population. Mindfulness training, with or without integrated meditation, body relaxation, acupressure, or distress intolerance components, has shown stable decreases in subjective distress, basal cortisol, and the amplitude/duration of physiological reactivity to a stressor (cortisol response, heart rate), within healthy controls (Bottaccioli et al, 2014; Fan, Tang, & Posner, 2014) and tobacco (Davis, Manley, Goldberg, Smith, & Jorenby, 2014; Goldberg et al, 2014), cocaine (Brewer et al, 2009; Kevin W Chen, Berger, Gandhi, Weintraub, & Lejuez, 2013), or alcohol abuse (Stasiewicz et al, 2013) treatment cohorts. Increased abstinence behavior and decreased cravings have likewise resulted from mindfulness or neurofeedback (biofeedback focused on electroencephalograms, EEG) training in substance abuse treatment (Kevin W Chen et al, 2013; Goldberg et al, 2014; Ross, 2013; Stasiewicz et al, 2013), including opioid addiction (Dehghani-Arani, Rostami, & Nadali, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual diagnosis with concurrent treatment of PTSD and substance use disorder has demonstrated overall improvement in outcomes (Back, Waldrop, Brady, & Hien, 2006; Mills et al, 2012; Najavits, Weiss, Shaw, & Muenz, 1998), but broader application of stress amelioration techniques may be advantageous in this population. Mindfulness training, with or without integrated meditation, body relaxation, acupressure, or distress intolerance components, has shown stable decreases in subjective distress, basal cortisol, and the amplitude/duration of physiological reactivity to a stressor (cortisol response, heart rate), within healthy controls (Bottaccioli et al, 2014; Fan, Tang, & Posner, 2014) and tobacco (Davis, Manley, Goldberg, Smith, & Jorenby, 2014; Goldberg et al, 2014), cocaine (Brewer et al, 2009; Kevin W Chen, Berger, Gandhi, Weintraub, & Lejuez, 2013), or alcohol abuse (Stasiewicz et al, 2013) treatment cohorts. Increased abstinence behavior and decreased cravings have likewise resulted from mindfulness or neurofeedback (biofeedback focused on electroencephalograms, EEG) training in substance abuse treatment (Kevin W Chen et al, 2013; Goldberg et al, 2014; Ross, 2013; Stasiewicz et al, 2013), including opioid addiction (Dehghani-Arani, Rostami, & Nadali, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness training, with or without integrated meditation, body relaxation, acupressure, or distress intolerance components, has shown stable decreases in subjective distress, basal cortisol, and the amplitude/duration of physiological reactivity to a stressor (cortisol response, heart rate), within healthy controls (Bottaccioli et al, 2014; Fan, Tang, & Posner, 2014) and tobacco (Davis, Manley, Goldberg, Smith, & Jorenby, 2014; Goldberg et al, 2014), cocaine (Brewer et al, 2009; Kevin W Chen, Berger, Gandhi, Weintraub, & Lejuez, 2013), or alcohol abuse (Stasiewicz et al, 2013) treatment cohorts. Increased abstinence behavior and decreased cravings have likewise resulted from mindfulness or neurofeedback (biofeedback focused on electroencephalograms, EEG) training in substance abuse treatment (Kevin W Chen et al, 2013; Goldberg et al, 2014; Ross, 2013; Stasiewicz et al, 2013), including opioid addiction (Dehghani-Arani, Rostami, & Nadali, 2013). Higher anxiety or distress has recently been found to increase willingness and perceived treatment efficacy for group stress reduction therapy in MMT (Barry et al, 2011), thus increasing feasibility of incorporating this training into existing intensive outpatient programs.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, there is only one report that has described the effect of mindfulness training on HCC. In a pilot study on smoking cessation, mindfulness training was compared with cognitive-behavioral therapy [35]. In that study, Goldberg et al reported lower HCC in the total sample after the interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several published examples of this type of study exist. In 18 participants who underwent a mindfulness or cognitive behavioral intervention for smoking cessation, Goldberg et al (73) showed a significant decrease in HCC between the hair segments corresponding to the period before the intervention, and the period after the intervention. The decrease was present in both treatment arms, and since no placebo group was present, a conclusion about the cause of the observed decrease cannot be drawn.…”
Section: Future Directionsmentioning
confidence: 99%